ACLS essentials - McKenna, Kim (McGraw Hill/Higher Education, 2008)
ACLS-Basics and More contains the "Cliff Notes" of the ACLS Provider Course, as well as essential info from the advanced resuscitation course. The textbook provide 60 illustrations, including approximately 20 rhythm strips for essential review. It also features 19 essential treatment algorithms. Appendices include a comprehensive medications table and a listing of common ACLS abbreviations. For each medication within the appendix, the following information is provided: action, uses, adult dose, common side-effects, and notes. In addition, within the medications table, ACLS medications and medication details for the experienced provider are italicized.